(untitled) (Journal of Emerging Technology in Teaching and Learning (JETTLe), 2025)
Mathematical literacy among junior high school students in Indonesia remains low due to limited educational resources that support its development. Many materials emphasize procedural mathematics rather than critical thinking and problem-solving, hindering real-world application. The STEM-Project-Based Learning (STEM-PjBL) approach addresses this by connecting mathematics to everyday life and integrating technology like GeoGebra™ for interactive learning. This study aims to develop a digital book incorporating STEM-PjBL and GeoGebra™ to enhance students’ mathematical literacy in Geometry. Using the ASSURE model, the research follows stages of analysis, objective setting, resource selection, learner participation, and evaluation. Expert validation confirms the digital book’s feasibility and effectiveness, with construct validity supporting its reliability in classrooms. This study is significant as it introduces an innovative learning resource that integrates STEM-PjBL with technology, fostering problem-solving and critical thinking. The findings suggest that interactive, project-based digital books can bridge the gap between theoretical knowledge and practical application, helping educators create engaging learning experiences and better prepare students for future academic and career challenges.